Hydro-actuation of ice plant seed capsules powered by water uptake. Issue 3 (September 2014) - Razghandi, Khashayar; Bertinetti, Luca; Guiducci, Lorenzo; Dunlop, John W. C.; Fratzl, Peter; Neinhuis, Christoph; Burgert, Ingo
Abstract : Unlike well-known plant hydro-actuation systems that respond to changes in relative humidity (RH) (e.g. wheat awns), ice plant seed capsules undergo a reversible origami-like unfolding and release their seeds only in response to exposure to liquid water. The engine for ice plant actuation was found to be the water uptake and swelling of a highly swellable cellulosic inner layer (CIL) inside the cell lumen of a hygroscopic tissue responsible for the unfolding movement. CIL was found to have an open structure with porous lamellae filling the gap between denser cellulosic mats. Thermogravimetric analysis of water–CIL interaction showed that the initial enthalpy-driven adsorption of water can only account for increasing the moisture content up to about 0·4 mg/mg, which is not sufficient to initiate the actuation. By applying a combined chemo-mechanical model, we could show that the entropic gain of the system through further water uptake (40–350 wt%) is sufficient to accomplish a full opening of the seed capsules through a sophisticated design at various hierarchical levels of the system. The principles behind this actuation mechanism may inspire the development of hydro-responsive devices that, although being highly hydrophilic, only respond to liquid water and not to changes in RH.